2022
DOI: 10.1038/s41467-022-30479-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition mechanism of the chloride channel TMEM16A by the pore blocker 1PBC

Abstract: TMEM16A, a calcium-activated chloride channel involved in multiple cellular processes, is a proposed target for diseases such as hypertension, asthma, and cystic fibrosis. Despite these therapeutic promises, its pharmacology remains poorly understood. Here, we present a cryo-EM structure of TMEM16A in complex with the channel blocker 1PBC and a detailed functional analysis of its inhibition mechanism. A pocket located external to the neck region of the hourglass-shaped pore is responsible for open-channel bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…We constructed mutants of this flexible residue with the aim to rigidify this region and investigated the consequence of the mutation on activation. The mutation of the equivalent position (i.e., Gly 510) in TMEM16A to a rigid proline, investigated in a previous study, has shown a pronounced right-shift of the EC 50 of Ca 2+ , reflecting a strong destabilization of the open state 42 . The concomitant weakening of its inhibition by an open-channel blocker, which binds to a close-by pocket that is formed in the active state, further underlines the restriction of conformational rearrangements by the mutation 42 .…”
Section: Resultsmentioning
confidence: 95%
“…We constructed mutants of this flexible residue with the aim to rigidify this region and investigated the consequence of the mutation on activation. The mutation of the equivalent position (i.e., Gly 510) in TMEM16A to a rigid proline, investigated in a previous study, has shown a pronounced right-shift of the EC 50 of Ca 2+ , reflecting a strong destabilization of the open state 42 . The concomitant weakening of its inhibition by an open-channel blocker, which binds to a close-by pocket that is formed in the active state, further underlines the restriction of conformational rearrangements by the mutation 42 .…”
Section: Resultsmentioning
confidence: 95%
“…The determination of the TMEM16A structure and elucidation of the gating mechanisms can now facilitate the rational drug design of small-molecule modulators acting on specific domains of the channel. Some of the recently identified small-molecule-binding sites involve the TM6 gate [11][12][13], and it remains to be determined whether molecules can be generated to selectively act on other functionally important regions of the channel. Like numerous other established drug targets, including ion channels [e.g., Ca v channels, ATP-sensitive K + (K ATP ) channels], TMEM16A is expressed in more than one tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…The binding sites for TMEM16A modulators remain largely undefined, although a combination of single point mutagenesis, electrophysiology, and molecular modelling led to the identification of putative binding sites for synthetic (e.g., A9C [11]) and endogenous (PIP 2 [9,10]) modulators (Figure 1). The structures of the TMEM16F [12] and TMEM16A [13] in the presence of either 1-hydroxy-3-(trifluoromethyl)pyrido[1,2-a]benzimidazole-4-carbonitrile (1PBC) [13], a potent inhibitor with antitumoral properties, or niclosamide have been obtained. The molecules bind to the extracellular-proximal end of TM6 (steric gate) of TMEM16F and TMEM16A [12,13], a region that also encompasses the A9C-binding site in TMEM16A [11].…”
Section: Pharmacodynamics Of Tmem16a Channel Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations